Lack of association between common polymorphisms associated with successful aging and longevity in the population of Sardinian Blue Zone - Alessandra Errigo; Maria Pina Dore; Giammarco Mocci; Giovanni Mario Pes (Scientific Reports)
Abstract More than two decades ago, in the central-eastern region of the Mediterranean island of Sardinia, a mountain area was identified where the population displays exceptional longevity, especially among men (the Longevity Blue Zone, LBZ). This community was thoroughly investigated to understand the underlying causes of the phenomenon. The present study analyzed 11 genetic markers previously associated with increased survival in several long-lived populations. APOE (rs429358 and rs7412), APOE promoter (rs449647, rs769446, and rs405509), ACE1 (rs1799752), IL6 ‒174G/C (rs1800795), TNFα ‒308G/A (rs1800629), FOXO3A (rs2802292), KLOTHO (rs9536314) and G6PD (rs5030868) polymorphisms were investigated. PCR-based genotyping was performed following genomic DNA extraction from 150 nonagenarians living in the LBZ and 150 controls from a nearby area. No significant deviation in the frequency of the analyzed markers was detected between the two subgroups except for a weak association with the − 174G > C gene variant in the IL-6 gene (p = 0.040), which codes for a major modulator of the inflammatory response. Overall, the findings of this study do not support a significant association of known genetic variants on survival in the population of the Sardinian LBZ, suggesting that other genetic or epigenetic traits not yet identified might play a role.